Typology of epos and ballad genres: «Koroghlu» and « Robin Hood» (Eurasian Journal of Philology Science and Education, 2019)
The epos of Robin Hood which had a number of variants and versions in the Middle Ages is a balladaccording to its genre. A ballad is a lyrical genre first of all, as this genre contains the features of poeticalnorm of the lyrical type. Besides possessing lyrical features, it has narrative and characteristics as well.The genre of ballad has both lyrical and epic features and it proves that lyrical and epic types have joinedin the structure in this genre. A ballad possesses not only the features of lyrical and epic types, but alsothe features of dramatic types. So, according to its origin a ballad is connected with folk dances, i.e. thedrama type of folklore. From the point of view of it is poetic structure the historical and cultural originof a ballad conveys the peculiarities epical lyric and dramatic types of folklore. This characteric featurecombines a ballad with the genre of epos from typological standpoint.